The first 2,000 days and child skills: Evidence from a randomized experiment of home visiting - Orla Doyle (University College Dublin, UCD School of Economics, 2017)
Using a randomized experiment, this study investigates the impact of sustained investment in parenting, from pregnancy until age five, in the context of extensive welfare provision. Providing the Preparing for Life program, incorporating home visiting, group parenting, and baby massage, to disadvantaged Irish families raises children's cognitive and socio-emotional/behavioral scores by two-thirds and one-quarter of a standard deviation respectively by school entry. There are few differential effects by gender and stronger gains for firstborns. The results also suggest that socioeconomic gaps in children's skills are narrowed. Analyses account for small sample size, differential attrition, multiple testing, contamination, and performance bias.
Keywords: C93; D13; I26; J13; 330; Early childhood intervention; cognitive skills; socio-emotional and behavioral skills; randomized control trial; multiple hypothesis testing; permutation testing; inverse probability weighting